FOTOMODELLAZIONE CON IMMAGINI DA SMARTPHONE PER LA DIFFUSIONE DELLA CONOSCENZA DEI BENI CULTURALI (GEOmedia, 2018)
Nell'era dell'high tech e della virtualizzazione diffusa risulta indispensabile avvalersi anche dei dispositivi mobili di uso comune per un nuovo modo di fare cultura e ricerca. La valorizzazione del patrimonio storico può – e deve – passare per la sua digitalizzazione low cost e user-friendly, se condotta in maniera consapevole e secondo protocolli di scientificità . Sant'Eligio al Mercato is the first gothic church built in Naples. The portal on the south side is the primary example of the influence of the Rayonnant style prevailing in Paris, the result of French workmanship and one of the few Late Medieval remains largely untouched in the numerous restorations over seven centuries. In this research, the portal is the case study of an investigation aimed to define and test the potential offered by three-dimensional reconstruction based on photogrammetric survey carried out with mobile device and with the goal of documenting and spreading the knowledge of cultural heritage.